LANGUAGE ENVIRONMENT BASED ON MULTIPLE INTELLIGENCES AT ISLAMIC BOARDING SCHOOL - Ridlo, Ubaid (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2019)
The purpose of this study was to find and analyze informal language environment based on multiple intelligences theory, and to find the achievements of Darul Muttaqien Islamic Boarding School Bogor in learning Arabic, both academic and non-academic achievements.This research was field research conducted at Tarbiyatul Mu'allimin wal Mu’allimât al-Islâmiyyah (TMI) class II and class V which is equivalent to the level of Madrasah Tsanawiyah class II and Madrasah Aliyah class II Darul Muttaqien Islamic Boarding School Bogor since July 2017 up to August 2018. This research was qualitative, using case study methods with steps: a) Analysis of findings continuously in the field, b) Grouping and organizing data, c) Making systematic notes and reading literature about other studies about relevant issues to obtain a framework that fits the findings in the field, and d) Evaluate each of the steps taken to avoid mistakes or sharpen the focus of the ongoing research. Data collection methods were in-depth interviews, participant observation, focus group discussions, and documentation. There were two types of data in this study: First, primary data was obtained from interviews, observation results, Focus Group Discussion results, and Lessson Plan/RPP/I'dâd Tadrîs, informal language environments, and learning evaluation. Second, secondary data is obtained from books, research journals, magazines, print and electronic media. This study proved that learning Arabic with Howard Gardner’s Multiple intelligences theory approach has a positive effect and very effective in improving students' language skills. Islamic boarding school with integrated, integrative and comprehensive education system has applied this theory in the process of learning Arabic, both in class and in the Islamic boarding school environment with the support of kyai, teachers, and representative facilities.